A new genus of Euthyplociinae from Ecuador (Ephemeroptera: Euthyplociidae) - Gonçalves, Inês C.; Pescador, Manuel L.; Peters, Janice G. (Zootaxa, 2020)
Three unusual nymphs of Euthyplociidae, subfamily Euthyplociinae, are described from Ecuador. A new genus and new species are established to accommodate these individuals. The morphologically unique specimens are defined by the following characters: short, stout tusks lacking spine-like setae but densely covered with long, hair-like setae; head almost as long as wide; long, quadrate clypeus with acute apicolateral projections; apex of 3rd segment of labial palp acute; apex of 3rd segment of maxillary palp acute and narrow. The hind wing is small, similar to that of Mesoplocia. An ongoing study of the phylogeny of the family recovers Dasyplocia gen. nov. as closely related to Euthyplocia and Mesoplocia.